Differentiate Thermal Property of Mammary Glands for Precise Photothermal Therapy. Issue 5 (11th March 2022) - Fang, Yuxin; Zheng, Weijie; Peng, Yuxuan; Liu, Jianhua; Gao, Jianshu; Tu, Yi; Sun, Shengrong; Huang, Xiaona; She, Jinjuan; Chen, Chuang; Xu, Shen; Yue, Yanan
Abstract: As an alternative to conventional methods, photothermal therapy is promising in breast cancer therapy. It is essential to prevent overheating of normal tissues and underheating of target tissues, which strongly depends on thermal transport processes. In this work, for the first time, the thermal properties of mammary glands in pubertal and mature mice is accurately measured. Thermal conductivity of mammary gland in pubertal mice is measured as 0 . 19 − 0 . 005 + 0 . 005 0.19 _ - 0.005^ + 0.005 W m −1 K −1, slightly higher than that of fat (0.17 W m −1 K −1 ), which is the main component of connective tissue in mammary glands. However, with the growth and pregnancy of mature mice, thermal conductivity of mammary gland increases to 0 . 32 − 0 . 004 + 0 . 004 0.32 _ - 0.004 ^ + 0.004 W m −1 K −1, 66.84% higher than that of pubertal mice. Numerical simulations are conducted to understand the role of thermal conductivity in photothermal therapy. The maximum temperatures in mammary glands of pubertal and mature mice are 49.6 and 44.6 °C, respectively, under the same laser irradiation conditions. This implies that higher thermal conductivity in mature mice mammary glands might lead to ineffectiveness in reaching to the desired temperature. This work suggests that age and pregnancy affect the thermal properties of mammary glands which are not negligible in breast cancer photothermal therapy. Abstract : A customized hot wire method is adapted in this work to investigate the thermal conductivity of mammary glands of pubertal mice and mature mice ex vivo. The effect of pregnancy and age on the thermal conductivity of mammary glands is significant through mathematical analysis. In addition, simulation results indicate that the difference in thermal conductivity can not be ignored in breast cancer photothermal therapy.